Effects of indoor and outdoor temperatures on blood pressure and central hemodynamics in a wintertime longitudinal study of Chinese adults. Issue 10 (8th October 2022) - Sternbach, Talia J.; Harper, Sam; Li, Xiaoying; Zhang, Xiang; Carter, Ellison; Zhang, Yuanxun; Shen, Guofeng; Fan, Zhongjie; Zhao, Liancheng; Tao, Shu; Baumgartner, Jill
Abstract : Objectives: We aimed to estimate the effects of indoor and outdoor temperature on wintertime blood pressure (BP) among peri-urban Beijing adults. Methods: We enrolled 1279 adults (ages: 40–89 years) and conducted measurements in two winter campaigns in 2018–2019 and 2019–2020. Study staff traveled to participant homes to administer a questionnaire and measure brachial and central BP. Indoor temperature was measured in the 5 min prior to BP measurement. Outdoor temperature was estimated from regional meteorological stations. We used multivariable mixed-effects regression models to estimate the within-individual and between-individual effects of indoor and outdoor temperatures on BP. Results: Indoor and outdoor temperatures ranged from 0.0 to 28 °C and −14.3 to 6.4 °C, respectively. In adjusted models, a 1 °C increase in indoor temperature was associated with decreased SBP [−0.4 mmHg, 95% confidence interval (CI): −0.7 to −0.1 (between-individual; brachial and central BP); −0.5 mmHg, 95% CI: −0.8 to −0.2 (within-individual, brachial BP); −0.4 mmHg, 95% CI: −0.7 to −0.2 (within-individual, central BP)], DBP [−0.2 mmHg, 95% CI:−0.4 to −0.03 (between-individual); −0.3 mmHg, 95% CI: −0.5 to −0.04 (within-individual)], and within-individual pulse pressure [−0.2 mmHg, 95% CI: −0.4 to −0.04 (central); −0.3 mmHg, 95% CI: −0.4 to −0.1 (brachial)]. Between-individual SBP estimates were larger among participants with hypertension. There was no evidence of an effect of outdoor temperature on BP. Conclusion: Our results support previous findings of inverse associations between indoor temperature and BP but contrast with prior evidence of an inverse relationship with outdoor temperature. Wintertime home heating may be a population-wide intervention strategy for high BP and cardiovascular disease in China.